Sugarcane Jaggery: An alternative of sugar for healthy living - Bhatt, Rajan; Kashyap, Lenika; Anuradha, Anuradha (Indian Farming, 2022)
Jaggery is better than sugar as far as nutritional values are concerned. Jaggery preparation not only provides additional nutrients in our diet but also adds to the overall income of the farmers which further improves their livelihood. Majority of the farmers produce jaggery with minimal capital input without caring about the scientific technique of jaggery preparation with value addition and also ignore the selection of sugarcane cultivars. Further, it is also critical to protect farmers’ profits by increasing both quantity and the quality of their jaggery units with value addition and current technology for packaging and jaggery-based products.